JURIDICAL REVIEW OF CRIMINAL ACTS OF DEFAMATION - Nurbaiti Syarif; Erik Kombi (Law Faculty of Universitas Bandar Lampung, 2022)
Criminal acts of defamation that occur in our society, need attention and handling by law enforcement officials. The juridical basis that regulates the criminal act of defamation is Article 310 and Article 311 of the Criminal Code (KUHP) which describe in detail the criminal act of defamation. For this reason, the author wants to know how the perspective of criminal law on defamation offenses and legal remedies in overcoming criminal defamation acts. This study uses a normative juridical approach which refers to the typology of research on applicable laws, norms, rules, regulations and legislation. The normative approach is carried out through library research by studying theoretical matters. The perspective of criminal law against perpetrators of criminal acts of defamation is applied based on Article 310 and Article 311 of the Criminal Code, which is seen from the point of view of the occurrence of prohibited acts, a person will be held accountable for his actions if the action is against the law and there is no reason to justify or negate the unlawful nature of doing so. crime committed and his ability to be responsible. Meanwhile, legal efforts in dealing with criminal acts of defamation can only be processed by the law enforcements if there are complaints from parties who feel that their names have been defamed.